“He believed that God could do everything, and that the Devil could do no more; but he also believed that the Devil could do the same as God in anything" : Bernabé Murillo and colonial witchcraft - Jauregui, Y.M.G.; Cahuas, F.A.V. (Universidad Cientifica del Sur, 2025)
The case of Bernabé Murillo demonstrates a slave transgressing the spaces of colonial Catholicism and seemingly prohibited interethnic relations. This individual was prosecuted twice by the Inquisition, being condemned the first time to exile and then as an idolater and heretic because it had been proven that he was not a neophyte in the faith and was fully aware of his transgressions, valuing the power of the devil and placing him on the level of God. Likewise, his network of clients was diverse and reveals that the uses of witchcraft were transversal to all social groups. However, by the 18th century, the Inquisition had a different logic for preserving the faith, deciding not to persecute those involved in witchcraft. Finally, we question the effectiveness of the evangelization process; we believe that a space like Callao helped recreate these heretical practices because religious control was diffused.
Keywords: Slavery; Bernabé; Murillo; Holy; Office; Witchcraft; Callao; https://purl.org/pe-repo/ocde/ford#6.01.01